Pragmatics of modern media text - Samusevich, Olga M. (Journal of the Belarusian State University. Journalism, 2019)
The article considers the pragmatic aspect of modern media text in its interrelation with the transformation of the paradigm of journalistic work. Functions of contemporary journalism are analyzed. A new type of journalism – interpretive one – is researched. Today this type of journalism possesses the greatest pragmatic potential in the process of public opinion formation. Ways of communicative influence (persuasion and suggestion) on mass consciousness as well as factors influencing the efficiency of communicative and pragmatic impact on audience are studied. The process of interpretation and its result – media picture of the world, the essence and structure of the interpretive model and peculiarities of interpretive fields formation in various mass media are characterized. The necessity of speech and cultural competence of journalists, their social responsibility for assessment and interpretation of the reality represented in a media product are defined.